Penerapan Model PBL Berbasis CRT untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas V Sekolah Dasar - Ngaini, Dwi Nur; Fadlillah, M.; Matwani, Matwani (YASIN, 2025)
This study is motivated by the low learning outcomes of fifth-grade students in the IPAS subject, particularly in Chapter 7 with the theme "My Region, My Pride," especially in Topic A, which discusses "What Is My Regional Culture Like?" The purpose of this research is to determine the improvement of learning outcomes for fifth-grade students through the implementation of the Problem Based Learning (PBL) model based on the Culturally Responsive Teaching (CRT) approach. This research is a type of Classroom Action Research (CAR) conducted in two cycles, with a research subject of 30 fifth-grade students at UPTD SDN Keleyan 1. Data collection techniques were carried out through observation and tests. The data obtained were analyzed descriptively using both quantitative and qualitative approaches. The results of the analysis indicate that the implementation of the CRT-based PBL model is effective in improving the learning achievement of students in the IPAS subject, Chapter 7. The average learning outcomes of students in the pre-cycle were 52.5; after cycle I, the average learning outcomes increased to 63.9, and in cycle II, they further increased to 75.0. Thus, it can be concluded that the CRT-based PBL learning model is capable of improving the learning outcomes of fifth-grade students in the IPAS subject at UPTD SDN Keleyan 1.